Development and Characterization of Glipizide Loaded Sustained Release Nanoparticles - Deshmukh, Rutuja; Waghulde, Mrunal; Mishra, Satyendra; Naik, Jitendra (Current Nanomedicine, 2019)
Background: Treating the disease like diabetes is essential due to its wide range of spreading and heredity issues. Glipizide is the commonly used drug for the treatment of diabetes. Glipizide loaded sustained release nanoparticles have been developed to avoid repeated dosing. Objective: The study aimed to develop glipizide-loaded sustained release nanoparticles and characterize them for different studies. Methods: The aim of the present study was to develop glipizide-loaded sustained release nanoparticles using different polymers by the solvent evaporation method. The polymers; Eudragit (RS 100) in combination with Polycaprolactone (PCL) were used to encapsulate glipizide. Optimization of all parameters was performed as per Design Expert software by utilizing a 32 full factorial design. The developed nanoparticles were characterized using Fourier transformed infrared spectroscopy, X-ray diffraction, scanning electron microscopy and in-vitro drug release study. Results: FE-SEM showed that the surface morphology of nanoparticles was smooth and spherical as well as in an oval shape. FTIR shows there is no interaction between polymers and drug. XRD results showed that the crystallinity of pure glipizide reduced from 89.5 to 56.7% when converted into sustained release nanoparticles formulation. Sustained drug release over the period of 12 h was observed due to well encapsulation of glipizide by the polymers. Conclusion: Glipizide loaded nanoparticles were developed with good encapsulation efficiency using a combination of two different biocompatible polymers. The drug release behavior showed that they can be used to develop the sustained release formulation to reduce the side effect caused by over drug uptake as compared to the conventional formulation.
Keywords: Glipizide